Two dogs in a trench coat start a club by accident - Falatko, Julie (Falatko, Julie. Two dogs in a trench coat., 2019)
Sassy and Waldo have continued wear a trench coat and attend school because they love being near their boy, Stewart, and because they particularly love lunch when they get to eat meat instead of kibble; now that Stewart has (reluctantly) joined the Junior Office Supply Enthusiasts club they get to stay later--but because of the lack of snacks the two dogs start exploring the empty cafeteria and end up starting a sandwich club.